NGLY1 mutation causes neuromotor impairment, intellectual disability, and neuropathy. - Çağlayan, Ahmet Okay; Comu, Sinan; Baranoski, Jacob F; Parman, Yesim; Kaymakçalan, Hande; Akgümüş, Gözde Tuğce; Caglar, Caner; Dölen, Duygu; Erson-Omay, Emine Zeynep; Harmanci, Akdes Serin; Mishra-Gorur, Ketu; Freeze, Hudson H; et al. (Eur J Med Genet, 2015)
N-glycanase 1 (NGLY1) is a conserved enzyme that is responsible for the deglycosylation of misfolded N-glycosylated proteins in the cytoplasm prior to their proteasome-mediated degradation. Disruption of this degradation process has been associated with various neurologic diseases including amyotrophic lateral sclerosis and Parkinson's disease. Here, we describe two siblings with neuromotor impairment, apparent intellectual disability, corneal opacities, and neuropathy who were found to possess a novel homozygous frame-shift mutation due to a 4 base pair deletion in NGLY1 (c.1533_1536delTCAA, p.Asn511LysfsX51). We hypothesize that this mutation likely limits the capability of neuronal cells to respond to stress due to accumulation of misfolded proteins, thereby impairing their survival and resulting in progressive loss of neurological function.
Keywords: Abnormalities, Multiple; Adolescent; Child; Corneal Opacity; Developmental Disabilities; Female; Frameshift Mutation; Genotype; Humans; Intellectual Disability; Male; Movement Disorders; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Peripheral Nervous System Diseases

Mutations in KATNB1 cause complex cerebral malformations by disrupting asymmetrically dividing neural progenitors. - Mishra-Gorur, Ketu; Çağlayan, Ahmet Okay; Schaffer, Ashleigh E; Chabu, Chiswili; Henegariu, Octavian; Vonhoff, Fernando; Akgümüş, Gözde Tuğce; Nishimura, Sayoko; Han, Wenqi; Tu, Shu; Baran, Burçin; Gümüş, Hakan; et al. (Neuron, 2014)
Exome sequencing analysis of over 2,000 children with complex malformations of cortical development identified five independent (four homozygous and one compound heterozygous) deleterious mutations in KATNB1, encoding the regulatory subunit of the microtubule-severing enzyme Katanin. Mitotic spindle formation is defective in patient-derived fibroblasts, a consequence of disrupted interactions of mutant KATNB1 with KATNA1, the catalytic subunit of Katanin, and other microtubule-associated proteins. Loss of KATNB1 orthologs in zebrafish (katnb1) and flies (kat80) results in microcephaly, recapitulating the human phenotype. In the developing Drosophila optic lobe, kat80 loss specifically affects the asymmetrically dividing neuroblasts, which display supernumerary centrosomes and spindle abnormalities during mitosis, leading to cell cycle progression delays and reduced cell numbers. Furthermore, kat80 depletion results in dendritic arborization defects in sensory and motor neurons, affecting neural architecture. Taken together, we provide insight into the mechanisms by which KATNB1 mutations cause human cerebral cortical malformations, demonstrating its fundamental role during brain development.
Keywords: Adenosine Triphosphatases; Animals; Brain; Cell Count; Cell Division; Dendrites; Drosophila; Drosophila Proteins; Humans; Katanin; Mice; Microcephaly; Microtubule-Associated Proteins; Mutation; Neural Stem Cells; Neurogenesis; Optic Lobe, Nonmammalian; Spindle Apparatus; Zebrafish